2020
DOI: 10.5653/cerm.2019.03349
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative live birth rate after up to three consecutive embryo transfer cycles in women with poor ovarian response

Abstract: Objective: In the present study, we aimed to retrospectively evaluate the cumulative live birth rate (LBR) after up to three consecutive embryo transfer (ET) cycles, either fresh or frozen, in women with expected poor ovarian response (ePOR). Methods: We selected 115 women who entered the first <i>in vitro</i> fertilization (IVF) cycle between August 2013 and July 2016. The women were divided into an ePOR group (37 women) and a non-ePOR group (78 women). All women in the ePOR group were ≥40 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
2
1
Order By: Relevance
“…After implementing POSEIDON criteria into clinical practice, many researchers have evaluated and compared ART outcomes among POSEIDON groups with or without normal ovarian responder and/or non-POSEIDON groups. The results differ between reported studies [17]- [23]. These studies include a variety of ethnicities ranging from Asian to Western countries.…”
Section: Discussioncontrasting
confidence: 74%
“…After implementing POSEIDON criteria into clinical practice, many researchers have evaluated and compared ART outcomes among POSEIDON groups with or without normal ovarian responder and/or non-POSEIDON groups. The results differ between reported studies [17]- [23]. These studies include a variety of ethnicities ranging from Asian to Western countries.…”
Section: Discussioncontrasting
confidence: 74%
“…Numerous studies have evaluated and compared ART outcomes among POSEIDON groups with or without referring to the “non-POSEIDON” group, which is conventionally named the “normal ovarian responder” group, and there were varying results 9 15 . These studies were based on patients of different ethnicities, including Asian and Western countries; however, to the best of our knowledge, no study has evaluated Korean patients according to the POSEIDON classification.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the POSEIDON group 2 showed a significantly higher pregnancy rate than its age-matched lower-ovarian-reserve counterpart group 4 ( p < 0.05, clinical pregnancy rates of 22.1% in group 2 and 4.8% in group 4). It has been well established that an AMH as low as 1.2 mg/mL is significantly correlated with poor ovarian response, especially in older patients 1 , 15 , 20 . Nevertheless, Tokura et al reported relative contraception probability among patients with POR over 40 years of age with AMH levels < 0.4 ng/mL 20 .…”
Section: Discussionmentioning
confidence: 99%